Contagious Yawning Among University Students - Najah Afina Mohd Harun; Muhammad Idris Bullare@Bahari (2020)
The purpose of this study was to examine the differences in the frequency of contagious yawning based on two aspects i.e. gender, social bond, and level of empathy measured by using Interpersonal Reactivity Index score. This study was conducted among University Malaysia Sabah students with 64 participants (male = 32, female = 32). The tools used include the Interpersonal Reactivity Index (IRI) used to measure empathy and a video that stimulate the yawn. The results summary shows that there is no difference in frequency for both gender and social bond. Meanwhile, empathy score prior to treatment and after treatment did not reveal any statistically significant outcome. Data was analysed by Mann-Whitney test and Paired samples t-test. The study found that both sexes, men and women have a sense of empathy within themselves. Limitations and other factors affecting human contagious behaviour are also discussed for future research purposes.